A Study of the Thermal and Mechanical Properties of Gelatin-based Bioplastics - Asia Neelam; . Omm-e-Hany (Current Advances in Geography, Environment and Earth Sciences Vol. 7, 2022)
Natural biopolymer proteins derived from fibrous insoluble collagen are widely used by a wide range of industries because of their ability to stabilize and to be handled easily. Scientists are interested in finding alternative polymers of plastic that provide food safety as well as being environmentally friendly. In this study, an investigation was carried out to determine the property of gelatin as a bioplastic polymer for substitute of synthetic film. This polymer is widely used as packing materials because of their good degradability and sustainability. In the laboratory, gelatin-based biofilms are produced by solution casting in petri dishes. The results of prepared biofilms shows week tensile strength (6.38 ± 0.20) and Break point elongation (611 ± 0.56) with activation energy 17 kJ/mol. However, 80% degradation achieved in gelatin biofilm with significant protection provided by gelatin coatings on food materials. Therefore, for strength, it is recommended that to be mixed with a certain amount of synthesis and gelatin polymer, so it meets all the packing industry’s performance requirements.